The Impact of Influencer Marketing on Consumer Decision-Making in E-Commerce Platforms - Samsu, Ridha Aprilla; Budiawan, Likha Navadiani; Yinnie, Celine; Muhroji, Jamal; Redjeki, Finny (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to analyze the influence of influencer marketing on consumer decision-making processes in e-commerce platforms. Utilizing a quantitative approach, the study investigates how influencer credibility, attractiveness, and expertise impact consumer purchase intentions. The research sample consists of 250 active e-commerce platform users in Indonesia. Data was collected through online questionnaires and analyzed using structural equation modeling (SEM). The findings reveal that influencer credibility significantly influences consumer purchasing decisions, with a path coefficient of 0.45 (p < 0.01). This study provides in-depth insights into the dynamics of influencer marketing in the digital era and its implications for consumer behavior in e-commerce environments.